Management of Wilms′ tumor: NWTS vs SIOP - Bhatnagar Sushmita (Journal of Indian Association of Pediatric Surgeons, 2009)
With the availability of several protocols in the management of Wilms′ tumor, there is dilemma in the minds of the treating oncologists or pediatric onco-surgeons as to whether the child should receive upfront chemotherapy or should be operated upon primarily. It is necessary for us to understand why do we follow either of the protocols, NWTS which follows the upfront surgery principle or the SIOP which follows the upfront chemotherapy principle in all stages of the disease. While deciding which protocol to follow, it is imperative to know the pros and cons of the treatment strategies and also to study the outcome patterns in both the treatment regimes which is what this article highlights. In an attempt to compare all the differences in both the major protocols, it was realized that most of our patients in the Indian scenario present with advanced disease and thus poorer outcomes if intensive and appropriate treatment strategies are not utilized. Hence, it is imperative that we should study our own patients through the Indian Wilms′ tumor study group and adopt the policies which improve the overall event free survival on a nationwide basis.